THE SIGNIFICANCE OF CERAMIC PRODUCTS IN INDUSTRY - Makhmudjon Ubaydullayev Akhmadjanovich (Western European Studies, 2024)
Ceramics have played a pivotal role in industrial development, thanks to their unique properties such as thermal resistance, durability, and chemical inertness. This article explores the multifaceted applications of ceramics in modern industry, delving into their use in electronics, construction, medical fields, and beyond. The discussion is supported by a review of current literature and highlights the challenges and opportunities in ceramic manufacturing. By understanding these dynamics, industries can better harness ceramics' potential for innovation and sustainability
Keywords: Ceramics; Industrial Applications; Thermal Resistance; Manufacturing